Cryptogenic ischemic stroke and prevalence of asymptomatic atrial fibrillation: a prospective study. Issue 12 (December 2016) - Jorfida, Marcella; Antolini, Marina; Cerrato, Enrico; Caprioli, Maria Giovanna; Castagno, Davide; Garrone, Paolo; Budano, Carlo; Cerrato, Paolo; Gaita, Fiorenzo
Abstract : Background: Atrial fibrillation is responsible for up to one-third of ischemic strokes, and is also associated with silent cerebral infarctions and transient ischemic attacks (TIAs). The self-terminating and often asymptomatic nature of paroxysmal atrial fibrillation (PAF) may lead to its underdiagnosis. A continuous and long-term heart rhythm monitoring can be useful in unmasking PAF episodes. Objective: Prevalence of asymptomatic PAF in patients suffering a cryptogenic stroke, at risk for atrial fibrillation but without any history of arrhythmia or palpitations, using a continuous electrocardiographic monitoring. Methods: One hundred and forty-two consecutive patients were admitted to the Stroke Unit of 'Città della Salute e della Scienza' Hospital of Turin between June 2010 and March 2013 and discharged with the diagnosis of ischemic cryptogenic stroke. Sixty fulfilled predefined inclusion criteria. Follow-up was carried on and completed for the 54 patients who consented to implantable loop recorder (ILR) implantation. After ILR implantation, trans-telephonic data were collected monthly. Results: Atrial fibrillation episodes lasting more than 5 min were recorded in 25 patients (46%), median detection time was 5.4 months (range 1–18) and median duration of atrial fibrillation episodes was 20 h (range 7 min–8 days) with 19 patients (76%) remaining asymptomatic and the others experiencing weakness and dyspnoea but not palpitations. Conclusion: Long-term heart rhythm monitoring is successful in unmasking silent atrial fibrillation in 46% of patients suffering a cryptogenic stroke with concomitant atrial fibrillation risk factors, but without history of arrhythmia or palpitations.